2012
DOI: 10.1017/s1460396912000349
|View full text |Cite
|
Sign up to set email alerts
|

The quality factor of x-rays/gamma rays as one is realistic?

Abstract: The quality factor for x-rays, gamma rays and electrons assigned as one need to be revised. It is observed that as the energy decreases, mean lethal radiation dose (Do)decreases as well and become more potent. It is therefore proposed that radiation quality in biological systems should be assessed in the mitotic phase of the cell cycles. Furthermore, based on the mean lethal radiation dose within specific energy range, an appropriate quality factor of x-rays, gamma rays and electrons should be assigned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Direct comparisons are also hampered by the different radiation exposure deliveries. Indeed, despite the fact that a quality factor of 1 is assigned for both x rays and gamma rays, the reliability of this assigned value has been called into question [ 20 , 21 ], more so for different tissues in vivo [ 21 ]. Within these acknowledged limitations, a tentative comparison is worth presenting, as it may help gain insights into this area of radiobiological research where much uncertainty persists.…”
Section: Discussionmentioning
confidence: 99%
“…Direct comparisons are also hampered by the different radiation exposure deliveries. Indeed, despite the fact that a quality factor of 1 is assigned for both x rays and gamma rays, the reliability of this assigned value has been called into question [ 20 , 21 ], more so for different tissues in vivo [ 21 ]. Within these acknowledged limitations, a tentative comparison is worth presenting, as it may help gain insights into this area of radiobiological research where much uncertainty persists.…”
Section: Discussionmentioning
confidence: 99%
“…10 For example, take cobalt 60 (Co-60) (1?25 MeV) RWF as one. Determine the mean lethal dose (Do) of a cell line in the mitotic phase of a given energy.…”
mentioning
confidence: 99%
“…This created an unprecedented problem in computing E. First of all, if we use RWF as 1, there is no differentiation/demarcation whether the exposure is in kV range or MV range or the calculated E is in kV or MV exposure. In addition, Akber 10 has shown that, as energy decreases, the potency of radiation at low energy increases. The relative biological effectiveness value increases as kV energy decreases.…”
mentioning
confidence: 99%
See 1 more Smart Citation